Bioinformatic and computational analysis for predominant mutations of the Nrf2/Keap1 complex in pediatric leukemia. Issue 12 (13th August 2021) - Akın-Balı, Dilara Fatma; Al-Khafaji, Khattab; Aktas, Sedef Hande; Taskin-Tok, Tugba
Abstract: The levels of reactive oxygen species (ROS) are tightly controlled and regulated by Nuclear Factor Erythroid-2-Like 2 (Nrf2) transcription factor, which is the main regulator of antioxidant responses and its suppressor protein Kelch-like ECH-associated protein 1 (Keap1). Our previous study has identified six novel changes in Nrf2/Keap1 pathway in pediatric ALL, which were described for the first time. These changes in the pathway are likely to alter the evolutionary process of amino acids and cause structural changes in the final products of genes. In this study, we aimed to compare the pathogenicity of eight determined mutations reported in our previous study by utilizing different programs with different algorithms and molecular dynamics simulation. Since it is too difficult to handle each existing mutation in a wet laboratory, in silico methods may give suggestion to choose the important mutations for further analysis and to establish the appropriate patient population and conduct wet laboratory studies. For this purpose, four different algorithms were used to evaluate the effects of single amino acid mutation. In addition, root-mean-square deviation, root-mean-square fluctuation and free-energy landscape analyses were performed to observe stability, flexibility and energetically favorable conformations, respectively, for each amino acid mutation. As a result, our study emphasizes the importance of Keap1 mutations in pediatric ALL Nrf2/Keap1 pathway, a total of eight mutations, two of which were shown for the first time in our study. Especially the mutations in the Keap1 Broad-Complex, Tramtrack and Bric-à-brac domain are worthy of attention. Communicated by Ramaswamy H. Sarma.